Servuy of Mental Health among Fire Department Employees of Shiraz city in 2016 - Mehdi JAHANGIRI; Azadeh SAFAIYAN; Sodabeh DASHTBESH PODONAK; Javad TAYEFE RAHIMIAN; Abdol-Halim RAJABI (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: Firefighting is among high stress jobs in which endanger their mental health. The purpose of this study was investigating the level of mental health in firefighters in Shiraz city. Methods: This cross-sectional study was conducted on 144 randomly selected firefighters in Shiraz. Required data were gathered using General Health Questionnaire (GHQ-28) and were analyzed by aid of SPSS 19. P-value less than 0.05 was considered statistically significant. Results: The average of age and experience of studied people was 35.03±7.66 and 10.88±6.11 years. Respectively, the average rating of mental health was calculated to be 30.79±12.44. According to the results of the study the percentage of healthy and those with light, mild and severe mental disorder among the studied firefighters were 23.8%, 58%, 16.8% and 1.4%. Conclusion: The results of this study showed that most of the studied firefighters were suspect to a degree of mental disorders. Considering the important role of firefighters in emergency situations, it is necessary to improve the level of their mental health.